Peningkatan Keterampilan Mengubah Puisi Menjadi Prosa Melalui Pendekatan Kontekstual Pada Siswa Kelas VI Sekolah Dasar - Pratiwi, Welly; F, Farida; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aim of this study is to describe the skills improvement of the sixth grade students at SDN 10 Bandar Buat Padang  in changing poetry into the prose, the stages are  pre-writing, writing, and post-writing. This type of research is a classroom action research that used qualitative and quantitative approaches. The results of this study indicate that the skill of turning poetry into prose has increased by 10,2%, which was obtained from the average value of the cycle I which is 79,1, increasing in the cycle II to 8,3. Based on these results, it can be concluded that using a contextual approach to the skill of changing poetry into prose of sixth grade elementary school students had increased.Keywords: Writing, Changing Poetry to Prose, Contextual